Functionalized conjugated polymer with plasmonic Au nanoalloy for photocatalytic hydrogen generation under visible-NIR. (21st May 2019) - Ghosh, Srabanti; Rashmi, Divya; Bera, Susmita; Basu, Rajendra N.
Abstract: Gold based multimetallic nanoalloys decorated on conjugated polymer nanofibers have been prepared using a greener approach without using any reducing agent. The as-prepared nanohybrids exhibited superior catalytic activity for solar hydrogen production under visible light (λ > 420 nm) irradiation and near infrared light irradiation. The UV–Visible diffuse reflectance spectra displayed strong absorption in the visible region which significantly favours the photocatalytic performance. Furthermore, the efficient charge separation suggested by electrochemical impedance measurement and photocurrent response curves for Au50 Pt24 Pd26 /PPy nanohybrids which exhibited significant enhancement in H2 generation rate compared to Au/PPy nanohybrids. The strong interface contact between Au nanoalloys and PPy nanofibers play an important role for the migration of electron during catalysis. The Mott–Schottky plot revealed that photo generated charge carrier concentration has been increased for Au50 Pt24 Pd26 /PPy nanohybrids (7.93 × 10 11 cm −3 ) compare to pure PPy (1.43 × 10 11  cm −3 ). The present study provides a new prospect for using conducting polymer based hybrid as photocatalysts for efficient solar hydrogen production. Highlights: Ananoalloy/PPy nanohybrids are developed by soft template method followed by radiolysis. Nanohybrids show strong absorption in visible and near infrared region and enhanced photoelectrochemical response. Nanohybrids demonstrates high photocatalytic H2 generation under visible and near infrared light. Enhanced charge separation and intimate interfacial contacts between Au NPs and PPy nanofibers enhances catalytic activity.